(untitled) (ADMPG Journal, 2020)
Brazil has been presenting progressive increases in sucide indexes, generating psychological, social and economic impacts, burdening both friends and family, and society itself. The present study deals with suicide and its relationship with workplace environment, relating it to knowledge about health, safety and well-being at work, Quality of Life at Workplace and its relationship with Corporate Social Responsibility focused on the internal environment. Its purpose is to identify workplace variables that correlate with suicide, as well as highlight the organization role and identify protective and worsening factors, through literature review, documentary research, and data collection through application of a semistructured questionnaire, with a qualitative quantitative approach, to young workers from Caxias do Sul, aged between 15 and 29. From the results achieved, it has been possible to conclude that: there are a large number of workers with risk for suicide; there are organizational factors that can result, or make worse, in illness or death; the organization may and must act in suicide prevention, independently of having responsibility in the psychic illness; bullying at work, and poor relationship with hierarchical superiors are risk factors for suicide; the employee access to qualified listener in the workplace is a protective factor against suicide.